Democracy and Reflections on 25 Years of Indonesian Reformation - Ahmad Naufal Afni Caya; Luqmanul Hakim (PT ARRUS Intelektual Indonesia, 2024)
Democracy has grown since the time of Ancient Greek civilization with the concept of Greek city states and Athens in 450 BC and 350 BC. Even in 431 BC, Pericles, a well-known Athenian statesman, defined democracy by putting forward several criteria: (1) government by the people with full and direct participation of the people; (2) equality before the law; (3) pluralism, namely respect for all talents, interests, desires and views; and (4) respect for a separation and personal area to meet and express individual personality (Roy C Macridis, 1983:19-20). In the same era, we can also get acquainted with the political thoughts of Plato, Aristotle, Polybius and Cicero, etc., to mention some of the thinkers of that time, who also laid the foundations for the notion of democracy. During its development, the concept of democracy underwent an increasing fertile phase and moved towards moderation during the Renaissance. So far, great thoughts have arisen about the relationship between the two rulers or the state on the one hand and the people on the other. There are new and surprising thoughts about the power and thought of Niccolo Machiavelli (1469-1527). On the Social Contract and the Separation of Powers by Thomas Hobbes (1588-1679), Jhon Locke (1632-1704). Many of these big names have thoughts of contributing significantly to efforts to redefine or implement the term democracy.